PSYCHOSOMATIC FEATURES OF PATIENTS WITH COMBINED UTERINE PATHOLOGY IN THE POSTMENOPAUSIS - Кравченко, Елена Николаевна; Безнощенко, Галина Борисовна; Заводова, Юлия Владимировна; Цыганкова, Ольга Юрьевна (Mother and Baby in Kuzbass, 2019)
Purpose of the study – to study the psychosomatic features of patients with a combined pathology of the uterus in postmenopause with the aim of developing a differentiated approach in the observation and treatment of this category of women. Material and methods of research. The main group (n = 59) consisted of patients with a combined pathology of the uterus and metabolic syndrome. The comparison group (n = 34) – patients with combined pathology of the uterus without the metabolic syndrome. To clarify emotional and affective disorders, everyone was examined by a psychiatrist, passed the Spielberg-Hamina test. Personality characteristics were assessed using the Accent-90-2 method. Neurovegetative, metabolic-endocrine and psycho-emotional disorders were assessed using a modified menopausal index. The results of the study. It was established that, from the psycho-emotional sphere, complaints were more often presented by patients of the main group (p < 0.001). In women with metabolic syndrome, greater severity of autonomic disorders was found in comparison with the data of the comparison group. A high level of reactivity of personal anxiety was revealed (p < 0.001) in women of the main group. These data are also confirmed by a high level of somatic vegetative disorders, which are probably a manifestation of the somatization of anxiety in women with metabolic disorders. Conclusion. During the opportunity assessment of correcting mental status, two of its variants should be considered, depending on the severity of the patient’s condition. The first variant is to receive basic therapy for combined uterine pathology, psychopharmacotherapy and psychotherapy. In the second variant, the basic treatment of the main gynecological disease in conjunction with psychotherapy can be prescribed.